Non-viral in vivo cytidine base editing in hepatocytes using focused ultrasound targeted microbubbles - Cynthia D. Anderson; Jennifer Ataam Arthur; Yuan Zhang; Nike Bharucha; Ioannis Karakikes; Ralph V. Shohet (Elsevier, 2023)
CRISPR-Cas9-based genome editing technologies, such as base editing, have the potential for clinical translation, but delivering nucleic acids into target cells in vivo is a major obstacle. Viral vectors are widely used but come with safety concerns, while current non-viral methods are limited by low transfection efficiency. Here we describe a new method to deliver CRISPR-Cas9 base editing vectors to the mouse liver using focused ultrasound targeted microbubble destruction (FUTMD). We demonstrate, using the example of cytosine base editing of the Pde3b gene, that FUTMD-mediated delivery of cytosine base editing vectors can introduce stop codons (up to ∼2.5% on-target editing) in mouse liver cells in vivo. However, base editing specificity is less than one might hope with these DNA constructs. Our findings suggest that FUTMD-based gene editing tools can be rapidly and transiently deployed to specific organs and sites, providing a powerful platform for the development of non-viral genome editing therapies. Non-viral delivery also reveals greater off-target base exchange in vivo than in vitro.